A FUNDAÇÃO MIRIM DE PRESIDENTE PRUDENTE COMO INSTITUIÇÃO EDUCACIONAL: UM ESTUDO DO INGRESSO DE JOVENS SOCIALMENTE DESFAVORECIDOS NO MERCADO DE TRABALHO - Nogueira, Fabio Luis (2006)
The present research aimed to demonstrate the influence caused by a program for the insertion of youth teenagers attended by the Mirim Foundation Presidente Prudente into the labor market. The theoretical basis for discussion and critical reflexive analysis in this research focused on studies that have demonstrated the major role played by non-governmental organizations (NGO), specially considering their organizational structure. Favorable aspects include the needs of a professional management in this kind of institution, and adequate approach of questions related to the job market, identifying significance, concepts and interferences of human activities in relation to the youth and to the interferences during their professional choice. We have carried on both: quantitative and qualitative research, by using semi-structured question sheets containing inquiries about the institution, the contents of the formative program and the professional reality of the formed youth. The questions have enabled identifying useful information that could be employed for the further analysis and discussion. The survey included 50 boys and girls formed in the last five years, chosen randomly. It was observed significance contribution to the creation of job opportunities, as well as in their professional growth. This research has indicated the existence of a feeling of gratitude in the youth, indicating that the goals aimed by the institution are relevant and that its structure is adapted with the developmental needs of the young people attended. It was demonstrated that the positive aspects pointed out by the formed youth have surpassed possible negative aspects, indicating that the institution is in time with the reality and changes of the globalized world.